Trudności przyswajania języka polskiego przez dzieci w wieku wczesnoszkolnym z doświadczeniem migracyjnym - Kushnir, Valentyna (Kultura-Społeczeństwo-Edukacja, 2025)
The topic of difficulties in acquiring the Polish language by early school-age children with migration experience, particularly from Ukraine, is extremely important in the context of contemporary challenges related to migration and integration. In the face of the armed conflict in Ukraine, many children have come to Poland in search of safety and better living conditions, which has introduced them to a new, unfamiliar environment where they must not only adapt culturally but also master Polish as the language of instruction. This study aims to investigate the problems faced by early school-age children with migration experience, striving to achieve bilingualism in Ukrainian-Polish or Russian-Polish. The research was conducted in two primary schools in Poznań with a group of 34 children. The research methods included observation, interviews with teachers, and surveys among parents. According to the theory of language acquisition, this process goes through various stages – from silence, through early forms of production, to intermediate and advanced fluency. Early school-age children from Ukraine who have been attending Polish schools for three years are often able to communicate in simple sentences but have difficulties with more complex language structures, which is reflected in their academic performance. Surveys conducted among parents indicate that most of them do not know Polish well enough to actively support their children in learning. Nevertheless, parents who engage in their children’s school life can notice improvements in their language skills. It is worth emphasizing that participation in additional Polish language classes has a positive impact on language acquisition. The study shows that children with migration experience have reached a level that allows them to communicate, but they still face difficulties in learning Polish. Limited vocabulary and insufficient exposure to Polish at home affect their ability to express thoughts. The school environment and parental support in the learning process are also crucial.